TECHNICAL KNOWLEDGE OF CREATING STEADY INLAY SHAPES IN SHADOW PUPPETS FOR BEGINNER INLAYS - Junende Rahmawati (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
This research aims to provide technical knowledge for parchment inlay to beginner inlays to produce steady inlay, which means constant or consistent. Through qualitative research with artistic research methods that discuss practice-based research that produces technical knowledge and understanding of inlays to produce inlays that are considered good. It is hoped that the technical knowledge of creating steady inlays that novice inlays pay attention to will provide clues that there are several things that need to be considered apart from continuous practice. It should be noted that the inlay results in the form of shadow puppets greatly influence the quality of beauty and aura of the puppet characters created. Apart from that, a good inlay will make the stitching process menyungging.